Estimating the air shower Xmax from radio measurements. (February 2019) - Revenu, B.; Dallier, R.; Escudie, A.; García-Fernández, D.; Martin, L.
Abstract: It is possible to use the radio signal emitted by air showers to estimate the primary cosmic ray characteristics, in particular its nature through the shower X max . The electric field emitted by air showers is computed assuming an atmospheric model; we need to know the air density and refractive index since these parameters have and influence on the development of the shower and the emitted electric field. We can get an unbiased estimation using the Global Data Assimilation System (GDAS) to compute the precise atmospheric conditions at the time and location an event is detected. We show how to use these data.